Pengaruh Pendapatan dan Usia Ibu yang Mempengaruhi Pemberian MP-ASI sebelum Bayi Berusia 6 Bulan si Puskesmas Wesaput - Farlikhatun, Lili; Tombi, Yudith Marianus (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT At the Wesaput Health Center, it was recorded that 70% of babies were given complementary foods (MP-ASI) before the age of 6 months, while only 204 babies received exclusive breastfeeding. A preliminary study on November 23, 2024, obtained from 15 mothers who had children under 6 months of age, as many as 8 respondents (53%) had been given MP-ASI to babies before the age of 6 months. This situation illustrates that the practice of giving MP-ASI to babies under 6 months of age (early MP-ASI) is still high. This phenomenon is influenced by several factors, including the lack of knowledge of mothers about the importance of exclusive breastfeeding, the circulation of myths about breast milk, and the busyness of working mothers. Giving MP-ASI before the time can interfere with the digestion of babies who are not ready to digest solid foods, which should only be accepted after the age of 6 months.  To determine the income and age factors that cause the provision of MP-ASI before the baby is 6 months old at the Wesaput Health Center in 2024.  Using a correlational analytical design with a cross-sectional approach. The sample consisted of 39 respondents with purposive sampling technique, and data analysis was carried out using the Chi-Square test. The results of the Chi-Square test showed a significant effect between income and the provision of complementary feeding, with a P-Value of 0.011 (p <0.05) and an Odds Ratio (OR) value of 0.918. Meanwhile, for maternal age, the results of the Chi-Square test also showed a significant effect between maternal age and the provision of complementary feeding with a P-Value of 0.057 (p <0.05) and an OR value of 0.813. There is a significant effect between maternal income and age on the provision of complementary feeding before the baby is 6 months old at the Wesaput Health Center in 2024. It is hoped that the Health Center and health cadres can increase more intensive counseling efforts regarding the importance of exclusive breastfeeding and the negative impacts of early provision of complementary feeding, especially for mothers with young age and low income. Keywords: Income, Age, Provision of MP-ASI Before The Baby Is 6 Months Old.     ABSTRAK Di Puskesmas Wesaput, tercatat bahwa 70% bayi diberikan makanan pendamping ASI (MP-ASI) sebelum usia 6 bulan, sementara hanya 204 bayi yang mendapatkan ASI eksklusif. Studi pendahuluan pada tanggal 23 November 2024 di dapatkan dari 15 ibu yang memiliki anak usia dibawah 6 bulan sebanyak 8 responden (53%) sudah diberikan MPASI pada bayi sebelum usia 6 bulan. Keadaan tersebut menggambarkan bahwa masih tinggi nya praktek pemberian MP-ASI pada bayi usia kurang dari 6 bulan (MP-ASI dini). Fenomena ini dipengaruhi oleh beberapa faktor, di antaranya kurangnya pengetahuan ibu tentang pentingnya ASI eksklusif, beredarnya mitos mengenai ASI, serta kesibukan ibu yang bekerja. Pemberian MP-ASI sebelum waktunya dapat mengganggu pencernaan bayi yang belum siap mencerna makanan padat, yang seharusnya baru dapat diterima setelah usia 6 bulan. Mengetahui faktor pendapatan dan usia yang menyebabkan pemberin MP-ASI sebelum bayi berusia 6 bulan di Puskesmas Wesaput tahun 2024. Menggunakan desain analitik korelasional dengan pendekatan cross-sectional. Sampel terdiri dari 39 responden dengan teknik purposive sampling, dan analisis data dilakukan dengan uji Chi-Square. Hasil uji Chi-Square menunjukkan adanya pengaruh signifikan antara pendapatan dan pemberian MP-ASI, dengan nilai P-Value sebesar 0,011 (p < 0,05) dan nilai Odds Ratio (OR) sebesar 0,918. Sementara itu, untuk usia ibu, hasil uji Chi-Square juga menunjukkan adanya pengaruh signifikan antara usia ibu dan pemberian MP-ASI dengan P-Value 0,057 (p < 0,05) dan nilai OR sebesar 0,813. Terdapat pengaruh signifikan antara pendapatan dan usia ibu terhadap pemberian MP-ASI sebelum bayi berusia 6 bulan di Puskesmas Wesaput pada tahun 2024. Diharapkan Puskesmas dan kader kesehatan dapat meningkatkan upaya penyuluhan yang lebih intensif mengenai pentingnya ASI eksklusif dan dampak negatif pemberian MP-ASI dini, khususnya bagi ibu dengan usia muda dan pendapatan rendah. Kata Kunci: Pendapatan, Usia, Pemberian MP-ASI Sebelum Bayi Berusia 6 Bulan.